2004
DOI: 10.1158/1078-0432.ccr-1016-03
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Immunity in Breast Cancer Patients Completing Taxane Treatment

Abstract: Purpose: A field study of postchemotherapy immune functioning relative to the use of taxanes is reported. Immune responses in breast cancer patients were analyzed as a function of whether patients received taxane as part of their adjuvant chemotherapy.Experimental Design: Immune levels of 227 stage II/III breast cancer patients were measured immediately after surgery prior to chemotherapy and again 12 months later when all chemotherapies had been completed. T-cell blastogenesis and natural killer (NK) cell lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 24 publications
1
56
0
3
Order By: Relevance
“…Moreover, data suggest that chemotherapy may favor the massive release of tumor associated neo-antigens, which follows cytotoxic-induced cell death (called immunogenic cell death) [41]; may suppress regulatory T cells, thus inhibiting the antitumor response; and may restore cytotoxic T cells [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, data suggest that chemotherapy may favor the massive release of tumor associated neo-antigens, which follows cytotoxic-induced cell death (called immunogenic cell death) [41]; may suppress regulatory T cells, thus inhibiting the antitumor response; and may restore cytotoxic T cells [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…61), which leads to Th1 activation and production of IFNg that has been implicated in control of cancer growth (62). Evidence also suggests that taxanes could exert an immunostimulatory effect against breast cancer (63)(64)(65)(66) by inducing a Th1 response. Paclitaxel has been shown to stimulate the secretion by macrophages of proinflammatory and Th1 cytokines such as IL1b or IL12 (67,68).…”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel has been shown to stimulate the secretion by macrophages of proinflammatory and Th1 cytokines such as IL1b or IL12 (67,68). Carson and colleagues (65) showed that in 227 breast cancer patients, T-cell activation was significantly higher in patients receiving taxanes compared with non-taxane-containing regimens. In contrast, anthracyclines primarily activate CD8 þ T cells rather than CD4 þ T cells to produce IFNg, as shown in mouse models (69).…”
Section: Discussionmentioning
confidence: 99%
“…Dual parameter flow cytometry for CD56 and the above mentioned cell surface markers was employed for characterization of the NK cell population [31]. PBMC were thawed and plated in complete medium at a density of 5 × 10 4 cells/well in 96-well U-bottom plates (Corning Incorporated, Corning, NY) in the presence of IL-2, IL-12, IL-15 (each at 20 ng/well) or control, and incubated for 24 hours (5% CO 2 , 37°C).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…adhesion molecules and KIR's). Dual parameter flow cytometry for CD56 and cell surface markers of NK cell lytic activity was used to characterize the effects of stress on the NK cell phenotype [31]. Cells were examined after 24 hour culture in media or in media supplemented with IL-2, IL-12, or IL-15.…”
Section: Comparison Of Nk Cell Receptor Expressionmentioning
confidence: 99%